Anthropogenic forcing and response yield observed positive trend in Earth’s energy imbalance - Shiv Priyam Raghuraman (Nature Portfolio, 2021)
Satellite observations reveal a significant positive trend in Earth’s energy imbalance, but the contributing drivers have yet to be understood. Here, the authors show that it is exceptionally unlikely that this trend can be explained by internal variability; instead, anthropogenic forcing and feedbacks cause the trend.